Playing for high steaks: Market structure and purchaser-led sustainbaility initiatives in the UK beef sector - Chris Foster; Sally Gee (The University of Manchester, Manchester Business School, 2013)
Large purchasers, or "focal organisations", exert considerable control over their value chains, particularly in the food sector. This paper draws on original qualitative research about the UK beef sector to explore how large purchasers are organising supply-chain eco-innovation. Livestock farming affects environmental sustainability in a number of ways and various initiatives aim to address these challenges. Through a 'fine-grained' analysis, focused on the organisational diversity of supply-chains within a single product group, we analyse how supply-chain structure conditions eco-innovative activity initiated by large purchasers. The paper extends the theory on buyer-driven commodity chains by considering how eco-innovation is influenced by the commercial importance of a product, as well as factors beyond the immediate supply-chain, such as government policy and consumer expectations. The paper concludes that although major retailers use their purchasing power to exert control over provision, they do not necessarily play a role in the governance of supply-chain eco-innovation.
Keywords: 330; eco-innovation; supply chain; UK beef sector; major retailers; purchasing power